Picture Word Inductive Model to Improve the Ability of the Procedure Writing of MTs Students - Nuning (IJOTL-TL: Indonesian Journal of Language Teaching and Linguistics, 2020)
This study aims to improve the students’ outcomes in learning to write English procedural texts through the Picture Word Inductive Model (PWIM). The research subjects were 27 students of MTs Negeri 1 Jepara. This research was conducted in 3 cycles in which the students worked in groups of four. In first cycle, the students describe a picture of a certain food or drink menu using the PWIM, while in second cycle the students explain the procedure of making food/drink recipes as in cycle 1. In the third cycle, the students ask for or provide information on food/beverage recipes using the PWIM. Data collection was carried out simultaneously with observation during the action, while the data analysis was carried out simultaneously at the time of reflection on the action. From the results of analysis/reflection, it reveals whether the action will be terminated (if it has reached the target) or continues to achieve the target. The data analysis was performed using the triangulation method. The results showed that there was an increase in student learning outcomes in participating in learning English writing with the PWIM. In the original situation, there were only 8 students (22.22%) out of 27 students who could describe certain objects/people/ places. In the first cycle of action, there were 10 students (37.04%) who could make the procedure text more correctly. In the second cycle, 17 students (62.96%) could write procedural texts correctly. In the third cycle, there was an increase in student learning outcomes. There were 27 students (100%) who could write the procedural text correctly.